PENDAMPINGAN PENYUSUNAN PERANGKAT PEMBELAJARAN IPS INTEGRASI KEARIFAN LOKAL SASAK POLA LESSON STUDY - Wadi, Hairil; Suud, Suud; Masyhuri, Masyhuri; Utomo, Jepri; Akbar, Ahmad Naufal (Universitas Mataram, 2025)
This Lecturer Community Service Program aims to improve the skills of social studies teachers in designing social studies learning materials integrating Sasak local wisdom using the Lesson Study method in Pujut District, Central Lombok. The first year of activities used expository methods, question-and-answer sessions, and discussions, and directly involved social studies teachers from junior high schools in the area. The results of the activities included: 1) The community service team delivered material on the concept of designing learning materials based on local wisdom using the Lesson Study method; 2) Social studies teachers were able to identify existing Sasak local wisdom that is still practiced by the community and integrated into learning materials; and 3) participants provided reflections on the activities. The output of this activity was a lecturer community service article, which was utilized by the community for the first year.